قصة سيدنا إسماعيل بين التوراة والقرآن - دراسة مقارنة - - توفيق, شرادي (جامعة الوادي university of eloued, 2019)
بيّنتُ في ىذه الدراسة أحداث قصة سيدنا إسماعيل )عليو السلام( ، في كلّ من القرآن الكريم والتوراة ، و قمتُ بعقد مقارنة بين أحداث القصة في الكتابين، مبيناً أنّ التوراة تتفق مع القرآن الكريم في بعض الجوانب؛ كرسم ملامح القصة العامة، ولكنّ اختلافهما كان أوسع وأشمل عند الحديث عن الجانب التفصيليّ، والقرآن الكريم ينفرد عن التوراة بالتركيز على مواطن العبرة والعظة في القصة، بينما تركز التوراة على السرد القصصي بعيداً عن العبر والعظات .وقد بيّنتُ التكريم الربانيّ لسيدنا إسماعيل )عليو السلام( في القرآن الكريم، والتهميش المتكررة لو في نصوص التوراة ، . ومن خلال ىذه الدراسة يتبين للقارئ الكريم كثرة التحريف والتزييف الممنهج في التوراة ؛ لما فيو من تعدٍّ على الله، وعلى نبيّو سيدنا إسماعيل )عليو السلام( ، مدللاً على الانحراف العقدي ا ولسلوكي لليهود في نظرتهم للرسل الكرام .وقد جعلت فهرساً للمصادر والمراجع وجعلتُ فهرس اً للآيات القرآنية ، وفهرساً للموضوعات،. سائلاً المولى عزّ وجلّ أن يجعل ذلك في ميزان حسناتي. Summary In this study, I explained the story of Sayyidina Ismail (peace be upon him), in the Holy Qur'an and the Torah, and I made a comparison between the events of the story in the two books, indicating that the Torah conforms to the Qur'an in some aspects such as the general story but their differences were broader and more comprehensive when we are talking about the small details of the story, The Holy Qur'an focuses on the morale and wisdom of the story, unlike the Torah that focuses on storytelling, away from lessons and sermons, also I have pointed out The divine honor of Ismail in the Qur'an, and the repeated marginalization of him in the texts of the Torah moreover this study I shown the readers the frequent and systematic distortion the Torah, and the insult for Allah (God) and the Prophet Ismail that contained it on it, in addition I pointed about the creed aberration and the behavioral deviation and of the Jews in their view of the Honorable messengers last but not least, I have made Index of topics, and index Quran verses, and made a index of sources and references. And in the end I hope god may accept this humble work
ليسانس